UJI AKTIVITAS ANTIBAKTERI DARI SEDIAAN KRIM EKSTRAK ETANOL HERBA TUMBUHAN BALSEM (Polygala paniculata L.) TERHADAP BAKTERI Propionebacterium acnes PENYEBAB JERAWAT - Helen Anjelina Simanjuntak; Kasta Gurning (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Acne is a skin disorder that occurs due to chronic inflammation, which is triggered by the growth of bacteria Propionibacterium acnes. The Balm plant (Polygala paniculata L.) is a small shrub originating from Indonesia. The purpose of this research is to determine the antibacterial activity of the formulation of a cream extract of the herbal ethanol extracts of the balm to the growth of bacteria Propionebacterium acnes. This research is an experimental study with five dosage formulations where the used concentration of extract consists of 0% (F1), 2% (F2), 4% (F3), 6% (F4), VitaCid as a positive control. The testing of antibacterial activity conducted by the CUP-plate technique method. Results showed that the extract of the balm plant in the preparation of cream could inhibit the growth of Propionibacterium acnes, visible with the formation of clear zones. The F1 cream preparations and F2 have stable and F3 categories, F4 has a dominant type.